2022
DOI: 10.1684/epd.2022.1487
|View full text |Cite
|
Sign up to set email alerts
|

Temporal encephalocele: a rare but treatable cause of temporal lobe epilepsy

Abstract: Objective. Although rare, temporal encephalocele is an important causative agent in surgically remediable drug‐refractory epilepsy. The ideal treatment for temporal encephalocele remains unclear with a variety of resective surgeries recommended. Here, we analyse patient data on temporal encephalocele with a view to highlighting diagnostic clues and management strategies. Methods. Comprehensive databases at Deenanath Mangeshkar Hospital, Pune from January 2015 to June 2019 were reviewed for this observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The epileptogenic potential of these lesions may be secondary to cortical irritation, secondary inflammation and gliosis and also associated lesions [1] . Multiple studies provide indirect evidence in support of this theory with reports of limited lesionectomy, corticectomy and bone repair resulting in favorable post-surgical outcomes [5] , [6] , [8] , [9] , [13] , [20] without removal of mesial temporal structures or neocortical temporal lobe structures typically resected in a standard anterior temporal lobectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epileptogenic potential of these lesions may be secondary to cortical irritation, secondary inflammation and gliosis and also associated lesions [1] . Multiple studies provide indirect evidence in support of this theory with reports of limited lesionectomy, corticectomy and bone repair resulting in favorable post-surgical outcomes [5] , [6] , [8] , [9] , [13] , [20] without removal of mesial temporal structures or neocortical temporal lobe structures typically resected in a standard anterior temporal lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the epileptogenic potential of encephaloceles and surrounding cortex presumed to be due to local irritation, traction, scarring or associated secondary lesions [1] . Several studies have noted favorable seizure outcomes with limited resections further providing evidence of the potential epileptogenicity of encephaloceles [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] . However, to our knowledge there is limited literature providing evidence with chronic intracranial monitoring that an encephalocele is in the seizure onset zone [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Yamazaki K et al published a case report about rare frontal encephaloceles presenting with epilepsy treated surgically. "Encephaloceles" are known to be associated with epilepsy, but mostly, they are located in the temporal lobe [34][35][36][37][38][39] and are rarely located in the frontal lobe [40,41]. The authors demonstrated the clear findings of the MRI, PET and electroencephalography of rare encephaloceles in frontal lobes and their successful surgical treatment via frontal lobectomy.…”
mentioning
confidence: 94%
“…They have been identified as a potential cause of temporal lobe epilepsy (TLE), but their epileptogenicity needs further confirmation. 1,2 The true prevalence of temporal encephaloceles (TEs) is likely underestimated. The largest case series to date estimates the prevalence to be between 2% and 4% in general presurgical evaluation of epilepsy patients and up to 10% in drug-resistant TLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Encephaloceles are herniations of brain tissue, typically occurring at the temporal pole in combination with skull defects of the sphenoid bone. They have been identified as a potential cause of temporal lobe epilepsy (TLE), but their epileptogenicity needs further confirmation 1,2 . The true prevalence of temporal encephaloceles (TEs) is likely underestimated.…”
Section: Introductionmentioning
confidence: 99%